Bis(silanetellurone) with C-H center dot center dot center dot Te Interaction - Ghosh, Moushakhi; Panwaria, Prakash; Tothadi, Srinu; Das, Aloke; Khan, Shabana (Inorganic Chemistry, 2020)
Herein, we report the synthesis of a series of bis(silanechalcogenones) [Ch = Te (2), S (3), or Se (4)] using an N-heterocyclic silylene-based SiCSi pincer ligand (1). 2 is the first example of a bis(silanetellurone) derivative. The bonding patterns of 2-4 were extensively studied by natural bond orbital, quantum theory of atoms in molecules, and noncovalent interaction index analyses, and these exhibit weak C-H center dot center dot center dot Ch interaction. The analogous reaction of 1 with trimethyl N-oxide produced a novel bis(cyclosiloxane) derivative (5). All of the complexes are duly characterized by single-crystal X-ray diffraction studies, multinuclear nuclear magnetic resonance (H-1, C-13, and Si-29) spectroscopy, and high-resolution mass spectrometry.

Harnessing strong chiroptical nonlinearity in carbene-copper-amides through center-specific chirality: an approach to amplified dissymmetry - Ghosh, Moushakhi; Tanwar, Riteeka; Panwaria, Prakash; Chatterjee, Abhijit; Panday, Rishukumar; Akhtar, Ruksana; Venugopal, Geethu; Mandal, Pankaj; Khan, Shabana (Journal of the American Chemical Society, 2026)
We present the design, synthesis, and photophysical characterization of a new class of chiral N-heterocyclic carbene (NHC)-copper(I)-amide (CMA) complexes with enantiomerically pure phenylethylamine motifs within the amide framework. These chiral CMA complexes represent a new class of mononuclear molecular Cu(I) complexes exhibiting pronounced chiral nonlinear optical (NLO) activity, which are actively being researched for advanced optoelectronic applications such as advanced photonics, biosensing, and security. The intrinsic molecular chirality and noncentrosymmetric crystal packing collectively enable strong second-harmonic generation (SHG) responses in the presence of circularly polarized (CP) light. Notably, these complexes display impressive SHG circular dichroism factors (g SHG-CD) as high as +/- 0.40 at 1000 nm, equaling or surpassing state-of-the-art chiral perovskites in this domain. Beyond their exceptional NLO response, the complexes exhibit dual emissive behavior, originating from both singlet and triplet excited states, with absolute quantum yields reaching 30%, and validated by TD-DFT calculations. The air-sensitive phosphorescence (similar to 550 nm) efficiently generates singlet oxygen (1O2), confirmed by PPh3 photooxidation and TEMPO radical generation. Remarkably, the emission can be reversibly switched between pure singlet and mixed singlet-triplet states by external modulation of O2, maintaining photostability over multiple oxic-anoxic cycles up to 5 days. These findings establish chiral CMA complexes as a new class of NHC-ligated molecular Cu(I) systems to display circularly polarized NLO activity with reversible photoluminescent switching, opening new avenues for exploring main-group organometallic compounds in next-generation polarization-sensitive photonic devices.